2018
DOI: 10.1002/jcb.27097
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis of missense mutations in galactokinase 1 (GALK1) leading to galactosemia type‐2

Abstract: Galactosemia type 2 is an autosomal recessive disorder characterized by the deficiency of galactokinase (GALK) enzyme due to missense mutations in GALK1 gene, which is associated with various manifestations such as hyper galactosemia and formation of cataracts. GALK enzyme catalyzes the adenosine triphosphate (ATP)-dependent phosphorylation of α-d-galactose to galactose-1-phosphate. We searched 4 different literature databases (Google Scholar, PubMed, PubMed Central, and Science Direct) and 3 gene-variant data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Some variants, including the one associated with the mildest known form of type II galactosemia (p.A198V), are expressed in reduced amounts by cells in comparison to the wild type [40,88]. Computational studies support the hypothesis that protein instability is a key factor in causing type II galactosemia [89,90]. Disease associated variants of UDP-galactose 4 epimerase are typically less stable then the wild type and, in some cases, have reduced affinity for the NAD + cofactor or aggregate in vivo [91][92][93][94][95][96].…”
Section: Potential In the Treatment Of Galactosemiamentioning
confidence: 89%
See 1 more Smart Citation
“…Some variants, including the one associated with the mildest known form of type II galactosemia (p.A198V), are expressed in reduced amounts by cells in comparison to the wild type [40,88]. Computational studies support the hypothesis that protein instability is a key factor in causing type II galactosemia [89,90]. Disease associated variants of UDP-galactose 4 epimerase are typically less stable then the wild type and, in some cases, have reduced affinity for the NAD + cofactor or aggregate in vivo [91][92][93][94][95][96].…”
Section: Potential In the Treatment Of Galactosemiamentioning
confidence: 89%
“…The definition of orphan drug differs depending on the jurisdiction, but it is largely dependent on the disease being rare and therefore a drug having little profitability, but which would meet a public health need. Orphan drug status can have benefits such as tax incentives, direct government subsidiary, increased patent time or a streamlined approval process [89].…”
Section: Costs and Returns On Investmentsmentioning
confidence: 99%
“…7). The mutational positions in the secondary structure of the proteins play an essential role in identifying structural alterations in the protein (Mosaeilhy et al 2017a; Mosaeilhy et al 2017b; Sneha et al 2018a; Sneha et al 2018b; Thirumal Kumar et al 2016; Yagawa et al 2010; Zaki et al 2017a). Alpha helices and beta strands are stabilized by hydrogen bonds (Schneider and Kelly 1995).…”
Section: Discussionmentioning
confidence: 99%
“…To increase in prediction accuracy of disease causing variants, we used Meta-SNP server (Capriotti et al 2013) that integrates four existing methods: PANTHER, SIFT, PhD-SNP, and SNAP to predict a mutation either disease (affecting the protein function) or neutral (having no impact). Further, a combination of these in silico tools and molecular dynamics studies in mutational analysis has been confirmed to be a dominant approach in understanding macromolecule behaviors and their microscopic interactions, allowing insights into the impact of mutations (Agrahari et al 2019; Ali et al 2017a; Ali et al 2017b; Nagarajan et al 2015; Sneha et al 2018a; Sneha and George Priya Doss 2016; Sneha et al 2018b; Thirumal Kumar et al 2019). Molecular dynamics (MD) aid in understanding the significant changes in the macromolecular structures of proteins due to mutations at an atomic level.…”
Section: Introductionmentioning
confidence: 99%
“…The GALK1 gene has 8 exons of 7.3 kb on chromosome 17q25.1.15 (2). GALK1 de ciency occurs worldwide but has a high frequency rate among the Roma (5). The important mutations of GALK1 gene which have pathogenic effect including P28T, A198V, V32M, G36R, R68C, R239Q, T288M, G346S, G349S, and A384P (18).…”
Section: Introductionmentioning
confidence: 99%